Seed germination ecology of doveweed (Murdannia nudiflora) and its implication for management in dry-seeded rice - Ahmed, Sharif; Opeña, Jhoana L.; Chauhan, Bhagirath S. (Cambridge University Press, 2015)
This study was conducted in the laboratory and screenhouse to determine the effects of temperature, light, osmotic stress, salt stress, burial depth, use of crop residues as mulch, depth of flooding, and use of POST herbicides on the emergence, survival, and growth of doveweed. In the light/dark regime, germination was higher at alternating day/night temperatures of 35/25 C (95%) than at 30/20 C (72%), and no germination occurred at 25/15 C. Light strongly influenced germination (95%) and dark completely inhibited germination. No germination occurred at an osmotic potential of −0.8 MPa and a salt concentration of 150 mM and above. The highest germination (91%) was observed from the seeds sown on the soil surface and emergence decreased by 78, 86, and 92% when burial depths were increased to 0.5, 1, and 2 cm, respectively. No seedlings emerged from seeds buried at depths of more than 2 cm. The use of rice residues as mulch significantly reduced the emergence and growth of doveweed seedlings. The amount of residue required to suppress 50% of the maximum biomass was 2.5 t ha−1. Flooding had a more pronounced effect on seedling biomass than seedling emergence. Biomass was reduced by 78, 92, and 96% when flooding depths increased from 0 to 2, 4, and 6 cm, respectively, for the seeds placed on the soil surface, whereas for the seeds buried at 0.5 cm, these values were 78, 100, and 100%. Bentazon (100 g ha−1) and bispyribac-sodium (30 g ha−1) provided 100% control of doveweed when applied at the three-leaf stage. Doveweed control was less than 31% with glyphosate rates up to 2,000 g ha−1. The application of 2,4-D (500 g ha−1) provided 100% control of doveweed even when applied at the seven-leaf stage. The information from this study could help in developing more sustainable and effective integrated weed management strategies for the control of this weed and weeds with similar response in dry-seeded rice systems.